Analysis of the Levels of Alteration of Aquifers Caused by the Installation of Wind Farms on Dunes on the Coast of Ceará, Brazil - Maria da Conceição Rabelo Gomes; Adryane Gorayeb; Dimas de Brito Souza; Raquel Morais Silva (Revista Ambiente & Água, 2019)
This research evaluated the levels of alteration of aquifers caused by installation of wind farms on dunes on the coast of Ceará, using the GOD and POSH methods of vulnerability, underground flow, and the application of multivariate analysis to subsidize the monitoring of groundwater quality in the area. There were three stages of field study: registering the wells and pollution sources, measuring the water levels, and groundwater sampling for laboratory analysis. The results obtained with the GOD method demonstrate the predominance of moderate- to high natural vulnerability of the aquifer to pollution in the areas close to the wind park in the district of Amarelas (Xavier and Ziu beach) and revealed high pollution loads according to the POSH method. The directional vectors of the underground flow are meaningful for Xavier Beach (high vulnerability), the center of Amarelas (moderate vulnerability), Tapuiu and Montevideo (low vulnerability). This indicated that the wind farm may have a potential impact on the lowering of groundwater in the area. From the multivariate analysis, it is evident that the groundwater characteristics are strongly related to the geological formation of the wells (Dunas and Barreiras), showing all samples within the Tolerable Maximum Value for human consumption for TDS, hardness, turbidity, and pH. It is vital to carry out preliminary studies of the aquifers underlying the areas where wind farms are to be installed, considering the levels of vulnerability and the risks of pollution and alteration of the water supply.